Avaliação da atividade antimicrobiana de dentifrícios à base de própolis sobre patógenos bucais. - SÁ, Tatiana Cerveira Valois de (2008)
Propolis has its properties widely reported in the literature, among them its antimicrobial property has been studied frequently in dentistry. Its incorporation to dentifrices aim to help in a more effective control and prevention of oral diseases by removing the biofilm and combating selective pathogenic species. However, few studies evaluated the effectiveness of dentifrices that contain propolis on the bacteria of the oral cavity. Thus, this work propuser to verify the in vitro antimicrobial action on Streptococcus mutans, Lactobacillus sp, Fusobacterium nucleatum, Aggregatibacter (Actinobacillus) actinomycetemcomitans, Enterococcus faecalis, and Candida albicans. The antimicrobial action of 3 dentifrices containing própolis, found on the market, was evaluated by the agar diffusion and dilution methods in triplicata. E. faecalis presented inhibition zones of 9.33 mm, 10.7 mm, and 14.3 mm of diameter. They were inhibited at the following dilutions, respectively: 1:1, 1:2 and 1:4. S. mutans presented halos of 9 mm, 28.3 mm, and 24.8 and was inhibited at the dilutions 1:1, 1:8, and 1:2 by Noplak, Protta, and Forever Bright, respectively. Noplak did not inhibit L. acidophillus, but Protta and Forever Bright produced inhibition halos of 11.5 mm and 12.3 mm. Noplak did not present antimicrobial activity against C. albicans, but Protta and Forever Bright formed halos of 10.7 mm and 10.2 mm. The inhibitory dilution was 1:1 in both cases. F. nucleatum and A. actinomycetemcomitans were not inhibited by any dentifrices tested. On the basis of the results obtained in this study it was concluded that the dentifrices Protta ® and Forever Bright ® possess inhibitoy action against S. mutans, E. faecalis, and C. albicans, whereas Noplak ® has a low antimicrobial activity, which is limited to S. mutans and E. faecalis.